Kenanga College Portal - Syed Adib, Wan Ali (Universiti Malaysia Sarawak (UNIMAS), 2019)
The project that is being discussed in this proposal is about a Kenanga College Portal which can turn the tides and ease the burden of students, instructor and staff of the college. Every project has its own challenge, some of my challenge is to gather the requirement of the system and apply it into the system. People like to do things online which is more time saving and effective way. The features like e-report and announcement can help the student to be more efficient of their time and does not need to que to get their service at the office. The students also can get fast and responsive feedback from the college staff for the progress of the repair. The college portal will be conducted using html programming language, JavaScript for the interaction and SQL server to test it ability in the server.